Effectiveness of an educational intervention of breast cancer screening practices uptake, knowledge, and beliefs among Yemeni female school teachers in Klang Valley, Malaysia: a study protocol for a cluster-randomized controlled trial - Noman, Sarah Noman Abdulrahman; Kadir @ Shahar, Hayati; Abdul Rahman, Hejar; Ismail, Suriani (MDPI, 2020)
Breast cancer is the most common cancer spread among women worldwide. Whereas many studies have discussed the significance of breast cancer screening among women in various countries, few have attempted to discuss this topic among female school teachers. As teachers educate and communicate with students, this may play an essential role in health education and in promoting healthy behavior, such as breast cancer screening. The primary goal of this study is to develop and implement an educational intervention of breast cancer screening and evaluate its effectiveness among Yemeni female school teachers in Malaysia. This was carried out as per the health belief model. A cluster-randomized controlled trial was conducted among 183 Yemeni female school teachers in twelve schools in Klang Valley, Malaysia. A random assignment of the target schools was made to include them within the intervention or control group. Participants in the intervention group were offered a 90-minute session for one-day educational intervention on breast cancer screening. On the other hand, participants in the control group were offered the same educational materials at the end of the study. Relevant data was collected at baseline, one month following the intervention, and then three- and six-months follow-up assessments. Analysis of such data was done via IBM SPSS software 25.0 by generalized estimating equations (GEE) to assess the differential changes over time. A primary outcome embodied in breast cancer screening practice uptake was expected. Secondary outcomes include the target group's knowledge on and beliefs of breast cancer screening. This study intends to contribute to the credibility and effectiveness of utilizing a theory-based breast cancer screening intervention in order to raise the awareness of women on conducting breast cancer screening.